2018
DOI: 10.1590/1983-21252018v31n415rc
|View full text |Cite
|
Sign up to set email alerts
|

SEED, SEEDLING AND FRUIT MORPHOLOGY AND SEED GERMINATION OF Psidium sobralianum PLANTS OF THE SÃO FRANCISCO VALLEY, BRAZIL

Abstract: The Northeast region of Brazil has the second highest number of species of the Myrtaceae family. It is mostly covered by the Caatinga biome, which is very degraded, making it difficult to preserve species of this family. Thus, the objective of this work was to describe the seed, seedling, and fruit morphology, and seed germination of Psidium sobralianum Landrum & Proença plants of the São Francisco Valley, Brazil. The fruits were collected in an area of the Brazilian Agricultural Research Corporation (Embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The MGTs observed in this study are lower than those observed by Gentil et al (2018) for P. friedrichsthalianum seeds and those observed by Santos et al (2004) for P. cattleyanum seeds submitted to different temperatures. The germination of the species is slow probably due to the mechanical barrier of the tegument, as observed by Freitas et al (2018) for P. sobralianum, which may have been altered with the increase of imbibition time. According to Masetto et al (2014), the soaking of P. guinean seeds is effective for increasing germination, with a TMG higher than that found in the present study.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The MGTs observed in this study are lower than those observed by Gentil et al (2018) for P. friedrichsthalianum seeds and those observed by Santos et al (2004) for P. cattleyanum seeds submitted to different temperatures. The germination of the species is slow probably due to the mechanical barrier of the tegument, as observed by Freitas et al (2018) for P. sobralianum, which may have been altered with the increase of imbibition time. According to Masetto et al (2014), the soaking of P. guinean seeds is effective for increasing germination, with a TMG higher than that found in the present study.…”
Section: Resultsmentioning
confidence: 83%
“…The yellow morphotype has a length of 3.67 mm (± 0.36 mm), a width of 2.81 mm (± 0.30 mm), and a thickness of 2.03 mm (± 0.27 mm). These values indicate that the seeds of P. cattleyanum are smaller than the seeds of other species of the same genus, such as P. sobralianum (length of 5.0 -7.0 mm) (FREITAS et al, 2018) and P. guajava (length of 2.70 -5.25 mm) (MISHRA et al, 2018). The size and shape of seeds are related to their dispersal strategy and are determinant for the establishment of seed or seedling banks.…”
Section: Resultsmentioning
confidence: 98%